مساهمة المؤسسات الصغيرة والمتوسطة في استحداث مناصب الشغل والتخفيف من حدة البطالة في الجزائر خلال الفترة (2002-2020) - قطوش, رزق (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقـة البحثيـة إلى تقديم قراءة عـن مدى مسـاهمة المؤسسـات الصـغيرة والمتوسـطة في التخفيف من حدة البطالة بالجزائـر خلال الفترة (2002-2020)، باعتبارها إحدى الآليات والنظم التشغيلية الجديدة التي أثبتت فعاليتها في التجارب الدولية، لما لها قدرة على خلق مناصب شغل لتقليص نسبة البطالة و تحقيق التنمية المستدامة والنمو الاقتصادي، وتوصلت الدراسة بناء على بيانات متحصل عليها من وزارة المؤسسات الصغيرة والمتوسطة متعلقة بنسبة مساهمة المؤسسات الصغيرة والمتوسطة في التوظيف إلى إجمالي العمالة المشتغلة وطنيا، إلى أن هذا القطاع الحيوي أصبح من الآليات الفعالة في خلق مناصب العمل وساهم في التخفيف من حدة البطالة في الجزائر وذلك من خلال تشجيع الشباب على انجاز مشاريع خاصة. This article aims to provide an interpretation of the contribution of Small and medium-sized enterprises (SMEs) to alleviating unemployment in Algeria during the period (2002-2020), as it is one of the new operational mechanisms and systems that have proven effective in international experiences, because of their ability to create jobs to reduce the proportion of joblessness and achieving sustainable development and economic growth The study, based on data obtained from the Ministry of Small and mediumsized enterprises related to the contribution of small and medium enterprises in employment to the total nationally employed labour, concluded that this vital sector has become one of the effective mechanisms in creating jobs and contributed to alleviating unemployment in Algeria, and that by encouraging young people to carry out special projects
The contribution of small and medium enterprises and its role in creating jobs and alleviating unemployment in Algeria during the period 2020-2002
مقال
Keywords: التشغيل؛ البطالة؛ المؤسسات الصغيرة والمتوسطة؛ الجزائر; employment; unemployment; small and medium enterprises; Algeria.